Gut Bacterial DNA Translocation is an Independent Risk Factor of Flare at Short Term in Patients With Crohn's Disease. (April 2016) - Gutiérrez, Ana; Zapater, Pedro; Juanola, Oriol; Sempere, Laura; García, Marifé; Laveda, Raquel; Martínez, Antonio; Scharl, Michael; González‐Navajas, José M; Such, José; Wiest, Reiner; Rogler, Gerhard; et al.
Abstract : OBJECTIVES: We aimed at evaluating bacterial DNA (bactDNA) presence in blood of Crohn's disease (CD) patients in remission as an independent risk factor of flare at 6 months. METHODS: This is a prospective, multicenter study on CD patients with Crohn's disease activity index (CDAI)<150. The primary end point was time‐to‐relapse as evaluated by CDAI>150 in the following 6 months. BactDNA in blood, the nucleotide‐binding oligomerization domain containing 2 ( NOD2 ) genotype, and serum cytokine levels were determined at baseline. RESULTS: A total of 288 patients were included. BactDNA was detected in 98 patients (34.0%). A variant‐NOD2 genotype was identified in 114 patients (39.6%). Forty patients (14%) relapsed during follow‐up. Multivariate survival analysis identified bactDNA as an independent risk factor of flare (hazard ratio (HR) 8.75 (4.02–19.06) 95% confidence interval (CI)). Hospitalization, surgery, switch of treatment, initiation and escalation of anti‐tumor necrosis factor (TNF) therapy, steroids initiation, and increased fecal calprotectin levels at 6 months were associated with bactDNA at baseline. A logistic regression analysis showed bactDNA as an independent and significant predictive factor of hospitalization (odds ratio (OR) 11.9 (3.4–42.3); P <0.001), steroids startup (OR 8.5 (2.7–27.1); P <0.001), and switch of treatment (OR 3.5 (1.6–7.7); P =0.002) at 6 months. No relationship was observed between bactDNA and mucosal lesions in patients with colonoscopy at admission. Serum pro‐inflammatory cytokines were significantly increased in patients with bactDNA or a variant‐NOD2 genotype. The combination of both factors induced decreased anti‐TNF‐α levels and a higher percentage of patients on intensified anti‐TNF therapy. CONCLUSIONS: BactDNA is an independent risk factor of relapse at 6 months in CD patients. BactDNA is also independently associated with an increased risk of hospitalization, switch of treatment, and steroids initiation.